Unravelling the complex interactions between self-awareness, cognitive change, and mood at 6-months post-stroke using the Y-shaped model - Wheeler, M; Williams, OA; Johns, L; Chiu, EG; Slavkova, ED; Demeyere, N (Routledge, 2022)
We investigated the relationships between cognitive change following stroke, awareness of cognitive impairments, and mood to further understanding of change processes influencing psychological outcomes post-stroke in line with the “Y-shaped” process model. Patients (n = 143; Mage = 73 years, SD = 13.73; 74 males) were assessed at 3-weeks (T1) and 6-months (T2) post-stroke and had completed the Oxford Cognitive Screen (T1 and T2), the Cognitive Failures Questionnaire (CFQ; T2), and the Hospital Anxiety and Depression Scale (HADS; T2). An ANCOVA controlling for disability relating to activities of daily living (ADL) revealed that awareness of cognitive impairment was significantly lower in participants with moderate-severe cognitive impairment. Regression analysis indicated that greater awareness of cognitive impairment and reduced independence in ADL were associated with greater emotional distress at T2. Cognitive improvement was associated with lower emotional distressat T2. Contrary to the awareness hypothesis, moderation analyses suggest that this effect was largest for those most cognitively impaired at T1. Findings emphasize the importance of monitoring stroke patients’ capacity to be self-aware when assessing and formulating long-term post-stroke distress and have potential implications for improving long-term emotional status in those most cognitively impaired post-stroke, e.g., through psychoeducation, cognitive rehabilitation, and emotional support.